Factors affecting the reliability of senior high schools’ english teacher-made test in Kebumen - Abdul Ngafif; Semi Sukarni; Ismawati Ike Nugraeni; Nelu Sahidah; Karin Dinda Pithaloka; Setiya Cahya Ningsih (LPPM Universitas Muhammadiyah Purworejo, 2022)
This study come up with the problem during the informal interview with the senior high school teachers. The researchers found that the teachers never check out whether the test they made reliable or not. They just find that the students’ score are high when the test done online and the score was low when the test done offline. This study aims to analyze the reliability and the factors affecting the reliability of senior high schools’ English teacher-made test in Kebumen regency. This research belongs to qualitative research, and it used descriptive case study. The instruments used by the researchers to get the data were documentation, close-ended questionnaires, and open-ended interviews. From the research, the reliability of the teacher-made tests are 0.839 (MAN 1 Kebumen), 0.747 (MAN 2 Kebumen), and 0.649 (MAN 3 Kebumen), so the test are reliable. Viewed from the questionnaires’ results, the factors affecting the reliability of the test are student-related reliability, rater reliability, test administration reliability, and test reliability. From the interviews’ results, the factors influencing the tests’ reliability are the mastery of learning material, the preparation of learning before getting the test, students' physical condition, the clarity of instructions of the test, clarity of questions in the test, the atmosphere and time allocation for doing the test.